Géographies spirituelles : mobilité des pasteurs pentecôtistes et « miracles » migratoires entre l’Afrique, l’Amérique Latine et l’Europe - Maïté Maskens (Brussels Studies, 2012)
By taking into account spatiality and identity in the movements of transnational religious stakeholders, this article intends to investigate the link between migratory and religious experiences as expressed by the ministers of four different Brussels-based Pentecostal congregations. The analysis of the ministers' narratives – reassessing the circumstances which led them from Sub-Saharan Africa or Latin America to Belgium – reveals an interwoven process of geographical shifts and “divine” actions, offering an opportunity to consider a twofold process involving mobility and religion. On the one hand, we can see how Pentecostalism transforms and subverts the migratory experience by allowing an alternative narrative of this experience. On the other hand, we are able to analyse the effect of this experience on the discourses and religious practices within the new environment, in particular through the identification process of the “Children of God”.